Mathematical model to predict vertical wicking behaviour”: Part II - Flow through woven fabric - Das, Brojeswari (2011)
The aim of the paper is to develop a mathematical model to predict vertical wicking behaviour of woven fabric. The first part of this series (Part I) has dealt with the mathematical model for predicting vertical wicking through yarn. In this part a model has been proposed to predict vertical wicking of the woven fabric, based on the developed yarn model. In order to model the flow through woven fabric along with the vertical flow through liquid carrying threads, the horizontal flow through transverse threads has also been taken into account. A simplified fabric geometrical concept (inclined tube geometry) and Peirce geometry for plain woven fabric have been used to define the fabric structure. Warp and weft linear density, fabric sett and yarn crimp have been considered in the fabric modelling. The theoretical wicking values of the yarn and fabric made from that yarn have been compared. Experimental verification of the model has been carried out using polyester and polypropylene fabrics. The model is found to predict the wicking height with time through the yarns and fabrics with reasonable accuracy